Social-Ecological Tipping Points of the Northern Humboldt Current Upwelling System, Economic Repercussions and Governance Strategies - (:unkn) unknown (My University, 2026)
The proposed project assesses the risk of decreases in marine ecosystem productivity as a tipping point for the interlinked ecological, economic and social systems of the Northern Humboldt Upwelling System (HUS). The extreme variability in climate-related